Roles of Parathyroid Hormone-Related Protein (PTHrP) and Its Receptor (PTHR1) in Normal and Tumor Tissues: Focus on Their Roles in Osteosarcoma - Al-Khan, Awf A.; Al Balushi, Noora R.; Richardson, Samantha J.; Danks, Janine A. (Frontiers in Veterinary Science, 2021)
Osteosarcoma (OS) is the most common primary bone tumour which originates from bone forming mesenchymal cells and primarily affects children and adolescents. The five-year survival rate for OS is 60% to 65%, with little improvement in prognosis since the last four decades. Studies have demonstrated the evolving roles of parathyroid hormone-related protein (PTHrP) and its receptor (PTHR1) in bone formation, bone remodelling, regulation of calcium transport from blood into the milk, regulation of maternal calcium transport to the fetus and reabsorption of calcium in kidney. These two molecules are also playing critical roles in the development, progression and metastasis of several tumors such as breast cancer, lung carcinoma, chondrosarcoma, squamous cell carcinoma, melanoma and OS. The expression of both PTHrP and PTHR1 have been demonstrated in OS, their function and proposed signaling pathways were investigated. Yet, their roles in OS have not fully elucidated. This review aims to discuss the latest research with PTHrP and PTHR1 in OS tumorigenesis and possible pathways. This review is dedicated to Professor Michael Day who died in May 2020 and was a very generous collaborator.